Review: The Role of Insulin in Aging: Mechanisms, Impact, and Therapeutic Perspectives (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2026)
Nanotechnology has emerged as a new, as a new approach to tackling antimicrobial resistance. AgNPs have been demonstrated. AgNPs have received extensive attention requiring their exceptional properties, such as chemical stability and of high quality conductivity. Unlike other metal nanoparticles, silver is non-toxic and harmless to the human body at low concentrations. These pathogenic bacteria exhibit several virulence factors, including the cytotoxic necrosis factor (colicin) and surface structures such as flagella and a capsule. They also possess cilia, which help them adhere to host tissues, enabling them to form biofilms. Given the importance of biofilms in the development of pathological infections and increased drug resistance, AgNPs  have    proven effective in inhibiting biofilm formation and secondary reactions. Scientists have been searching for a suitable method to control and prevent the growth of biofilms, given their good compatibility with a mixture of AgNPs. Studies have shown that the diameter of the nanoparticles affects the bacteria. ConclusionAntibiotic resistance patterns raise concerns about the emergence and resurgence of multidrug-resistant pathogens. Developing or modifying antimicrobial compounds to improve their ability to kill bacteria is a modern priority. Nanotechnology provides effective principles for improving and developing nanostructures with promising applications in various fields. These silver nanoparticles have proven effective as weapons against potent biofilm producers, such as E. coli, which causes urinary tract infections. These particles can also be used synergistically with certain antibiotics, increasing the effectiveness of the antibiotic against bacterial resistance.